Educating the supply chain: an holistic approach. (4th August 2014) - Evans, G.N.; Naim, M.M.; Towill, D.R.
Supply chain management is currently perceived as the means of enabling successful international competitive advantage. Considerable interest has been directed at strategic and structural levels on the cost implications of poor dynamic behaviour generated by delays, distortion and noise within various levels of the supply chain. While the principle of dynamic behaviour is recognised from individual in–house experiences, the effects on the total supply chain performance are less well known. With companies operating in increasingly competitive environments, there is an educational need to realize the consequences of in–house redesign strategies on the dynamics of the whole supply chain. Research by the Logistics Systems Dynamics Group (LSDG) in Cardiff has shown the value of using the Ingersoll Engineering adage of 'simplify – integrate – automate' in re–engineering supply chains. System simplification leads to considerable insight into the generating mechanisms of poor business operation which would be difficult to detect due to the original complexity. It is argued that systems integration must evolve at a strategic level, prior to automation. At the same time attitudinal changes instigated at the local level ensure the successful implementation of management change.